Perancangan Mebel Knockdown yang User-Friendly untuk Ruang Tamu - Steven Wibowo (Intra, 2016)
In America, the price of land for a dwelling house is very high, so many new families or who can be called as a gen x and gen y choose to stay in the apartment, but most of them have goal to move into a landed house. Overseeing that issue, it needs a furniture that is durable and easily moved. Based on that, came an idea to create a furniture which has a light weight and easy to assembly. In this thesis, the furniture is mainly created for the living room area, because according to a research held by IKEA, living room’s furniture is ranked first for the most favourable furniture in public. Living room also regarded as one of the most important rooms in a house. As a basic for workmanship, this design is pass through several stages, i.e. the study of literature, data and qualitative observations, programming, design concepts, sketches and schematic design, mock-up, development, final design, and manufacture of prototype 1: 1. This design has five sets of options with differences in knockdown construction that is used in each furniture. The fifth set is intended to ease in disassembling the furniture for users. Apart from that, safety for users is also considered while designing this furniture.